Between script and scripture: performance criticism and Mark's characterization of the disciples - Eberhart, Zechariah (Biblical Interpretation Series, 2024)
"This volume reimagines the first-century reception of the Gospel of Mark within a reconstructed (yet hypothetical) performance event. In particular, it considers the disciples' character and characterization through the lens of performance criticism. Questions concerning the characterization of the disciples have been relatively one-sided in New Testament scholarship, in favor of their negative characterization. This project demonstrates why such assumptions need not be necessary when we (re-)consider the oral/aural milieu in which the Gospel of Mark was first composed and received by its earliest audiences"--